Pengetahuan Dan Tindakan Orang Tua Dalam Perawatan Gigi Susu - Ady Imanuel Ismaua; Christina Ngadilah; Ferdinan Fankari; Applonia Leu Obi (Poltekkes Kemenkes Kupang, 2019)
Abstract: Knowledge and Actions of Parents in Primary Teeth Care.Dental and oral health is part of the health of the body that can not be separated from one another. Because oral health will affect the health of other bodies. Dental health is important because food digestion starts with the help of teeth which are useful for the normal growth and development of children. Therefore, parents must have good knowledge of baby teeth. But